An Ipomoea batatas iron-sulfur cluster scaffold protein gene, IbNFU1, is involved in salt tolerance. - Degao Liu; Lianjun Wang; Chenglong Liu; Xuejin Song; Shaozhen He; Hong Zhai; Qingchang Liu (PLoS ONE)
Iron-sulfur cluster biosynthesis involving the nitrogen fixation (Nif) proteins has been proposed as a general mechanism acting in various organisms. NifU-like protein may play an important role in protecting plants against abiotic and biotic stresses. An iron-sulfur cluster scaffold protein gene, IbNFU1, was isolated from a salt-tolerant sweetpotato (Ipomoea batatas (L.) Lam.) line LM79 in our previous study, but its role in sweetpotato stress tolerance was not investigated. In the present study, the IbNFU1 gene was introduced into a salt-sensitive sweetpotato cv. Lizixiang to characterize its function in salt tolerance. The IbNFU1-overexpressing sweetpotato plants exhibited significantly higher salt tolerance compared with the wild-type. Proline and reduced ascorbate content were significantly increased, whereas malonaldehyde (MDA) content was significantly decreased in the transgenic plants. The activities of superoxide dismutase (SOD) and photosynthesis were significantly enhanced in the transgenic plants. H2O2 was also found to be significantly less accumulated in the transgenic plants than in the wild-type. Overexpression of IbNFU1 up-regulated pyrroline-5-carboxylate synthase (P5CS) and pyrroline-5-carboxylate reductase (P5CR) genes under salt stress. The systemic up-regulation of reactive oxygen species (ROS) scavenging genes was found in the transgenic plants under salt stress. These findings suggest that IbNFU1gene is involved in sweetpotato salt tolerance and enhances salt tolerance of the transgenic sweetpotato plants by regulating osmotic balance, protecting membrane integrity and photosynthesis and activating ROS scavenging system.